2012
DOI: 10.21009/jpensil.v1i2.9820
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Sistem Pembelajaran Blok Tri Wulan Pada Mata Pelajaran Produktif Program Keahlian Bangunan SMKN 1 Jakarta

Abstract: This research purposed to find the effectiveness of productive course subject using Three-Months-Blocking learning system at SMKN 1 Jakarta majoring in technical construction drawing. Seen from many obstacles happened during the process Three-Months-Blocking learning system at SMKN 1 Jakarta, we were interested in examining the effectiveness of the Three-Months-Blocking learning system. The research duration is on April until June 2012. The survey method was taken into consideration to find the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The implementation of the block system had a positive and effective effect in secondary schools. Kurniawan and Karsono (2012) stated that the Tri Wulan Block Learning System has effectively applied in SMKN 1 Jakarta, especially in Building Drawing Engineering Subjects. The overall results of this study can be concluded that the Tri Wulan Block Learning System implemented by SMKN 1 Jakarta, especially in the Productive Subjects of the Building Engineering Skills Program from the beginning of July 2011 until the end of June 2012 is effective.…”
Section: Qualitative Data Descriptionmentioning
confidence: 99%
“…The implementation of the block system had a positive and effective effect in secondary schools. Kurniawan and Karsono (2012) stated that the Tri Wulan Block Learning System has effectively applied in SMKN 1 Jakarta, especially in Building Drawing Engineering Subjects. The overall results of this study can be concluded that the Tri Wulan Block Learning System implemented by SMKN 1 Jakarta, especially in the Productive Subjects of the Building Engineering Skills Program from the beginning of July 2011 until the end of June 2012 is effective.…”
Section: Qualitative Data Descriptionmentioning
confidence: 99%
“…Sistem blok merupakan suatu sistem pembelajaran dengan jam pembelajaran diatur atau dikelompokkan menjadi lebih panjang dari biasanya dan bertujuan agar peserta didik dapat belajar lebih maksimal [5]. Sistem blok diartikan sebagai sistem tuntas mata pelajaran dengan jumlah jam berdasarkan ketentuan yang ada di kurikulum serta disepakati bersama dengan pihak sekolah [6]. Bisa disimpulkan bahwa sistem pembelajaran blok merupakan sistem yang pelaksanaan pembelajarannya dengan cara mengelompokkan jam pembelajaran dari beberapa pertemuan menjadi satu kali pertemuan berdasarkan pada pembagian jam untuk tercapainya tujuan pembelajaran berdasarkan tuntutan kurikulum.…”
unclassified